Pemberdayaan Masyarakat Loji, Kota Bogor dalam Pencegahan Stunting Melalui Program Perisai Keluarga dan Percepatan Kebun Stunting - Salsabila, Kania; Sambogo, Rizki Bagus; Syahrani, Iga Dwi; Fajar, Muhammad Rizky; Aisya, Zalfa Rihadatul; Dewi, Maharani Arzela; Sarah, Wurianty; Annisa, Apriyanti Nur; Putra, Hilal Rosyid; Hasibuan, Lailan Sahrina (Jurnal Pusat Inovasi Masyarakat, 2024)
The nutritional problems that are still inherent in Indonesia, especially stunting among toddlers, have had a serious impact on the quality of human resources. Loji Subdistrict in Bogor City is facing problems related to increasing stunting rates, which has sparked action from IPB students through the KKN-TI program to help reduce stunting rates. This program is carried out in the form of education and planting of family medicinal plants, cultivating fish in buckets (budikdamber) based on aquaponics, as well as cooking demonstrations using ingredients from family medicinal plants, through a program called Perisai Keluarga and Acceleration of Stunting Gardens. The success indicator of the Perisai Keluarga with the Loji BERTOGA subprogram is the achievement of the Family Medical Plant (FMP) planting process with a minimum of three types of plants and conveying an understanding regarding the benefits of these plants, Perisai Keluarga with the Gandeng PMT-ji subprogram was said to be successful with a percentage of 80% of toddlers liking the churros and moringa leaf sauce menu as well as Trilaa tea, the high level of enthusiasm of the mothers when they took part in the cooking demonstration, and received the Supplementary Feeding Program (SFP) recipe menu book, while the Stunting Garden Acceleration was said to be successful by achieving the resumption of installation of catfish cultivation in buckets based on aquaponics. It is hoped that this activity can improve community nutrition, reduce stunting, and encourage awareness of the importance of balanced nutrition.